(untitled) (TSUL LEGAL REPORT, 2026)
The growing integration of artificial intelligence (AI) and robotics into various sectors of society raises complex legal and ethical questions about their status within traditional legal frameworks. This study critically examines the concept of legal personhood for AI and robots by analyzing classical theories, pragmatic models, and emerging policy proposals. While traditional theories tie personhood to autonomy and moral agency, pragmatic approaches suggest that functional legal recognition may be necessary to address accountability gaps created by autonomous systems. The study advocates for establishing a new category of “electronic agents” endowed with limited rights and strict liabilities, designed to facilitate legal interactions without undermining human dignity or rights. Through doctrinal and comparative legal analysis, this research highlights the urgent need for international harmonization of AI regulations to prevent jurisdictional fragmentation. The findings support a cautious, balanced expansion of legal subjectivity that accommodates technological evolution while preserving core ethical principles. By proposing practical, ethically sound frameworks for AI legal integration, this study contributes to the broader discourse on the future of law in an AI-driven world.